Recontextualizing Islamic Inheritance Law in the Contemporary Era: An Uṣūl al-Fiqh Perspective and the Responses of Urban Muslim Communities - Khoirul Amru Harahap; Ahmad Rezy Meidina; Muhammad Fuad Zain; Imam Sibawaih (Legitima : Jurnal Hukum Keluarga Islam, 2026)
Purpose – This article explores the recontextualization of Islamic inheritance law through the perspective of uṣūl al-fiqh, focusing on the reformist ideas of Munawir Sjadzali and their reception among urban Muslim communities in Purwokerto, Indonesia. It seeks to examine how contemporary Muslim communities negotiate classical inheritance doctrines in response to changing social realities and evolving notions of justice and gender equality. Methods – This study employs a qualitative approach by combining library research on Munawir Sjadzali’s concept of inheritance reform with fieldwork involving in-depth interviews with twelve informants, including religious leaders, Islamic legal practitioners, academics, and Muslim families. The analysis is framed through the principles of maqāṣid al-sharī‘ah and maṣlaḥah to interpret contemporary understandings and applications of Islamic inheritance norms. Findings – The findings reveal three distinct patterns of community responses to inheritance reform. Progressive groups support contextual reinterpretation by emphasizing gender equality, women’s economic participation, and substantive justice, reflecting Sjadzali’s reformist orientation. Moderate groups accept limited adjustments under specific familial and social circumstances while maintaining the Qur’anic inheritance ratios as the normative foundation. In contrast, conservative groups reject reinterpretation and uphold classical jurisprudential formulations as immutable religious prescriptions. These patterns demonstrate that public acceptance of inheritance reform is closely associated with differing understandings of uṣūl al-fiqh principles and the legitimacy of contextual ijtihād. Research implications/limitations – This study contributes to contemporary debates on Islamic legal reform by demonstrating how uṣūl al-fiqh can mediate between normative religious texts and evolving social realities in the recontextualization of Islamic inheritance law. However, the findings are limited to urban Muslim communities in Purwokerto and may not be generalizable to other socio-cultural contexts in Indonesia.